Strategies for Reforming Korea's Labor Market to Foster Growth - Dao, Mai (IMF Working Papers; Working Paper, 2014)
While the Korean unemployment rates are currently among the lowest in OECD countries, the labor market duality and the underemployment in some segments of the population are important labor market challenges, and factors contributing to lower potential growth. The paper shows the benefits of comprehensive policy reforms aimed at increasing labor force participation and youth employment and reducing duality are likely to be considerable in the medium term.